Accelerating locomotor recovery after incomplete spinal injury. (26th March 2013) - Hillen, Brian K.; Abbas, James J.; Jung, Ranu
Abstract : A traumatic spinal injury can destroy cells, irreparably damage axons, and trigger a cascade of biochemical responses that increase the extent of injury. Although damaged central nervous system axons do not regrow well naturally, the distributed nature of the nervous system and its capacity to adapt provide opportunities for recovery of function. It is apparent that activity‐dependent plasticity plays a role in this recovery and that the endogenous response to injury heightens the capacity for recovery for at least several weeks postinjury. To restore locomotor function, researchers have investigated the use of treadmill‐based training, robots, and electrical stimulation to tap into adaptive activity‐dependent processes. The current challenge is to maximize the degree of functional recovery. This manuscript reviews the endogenous neural system response to injury, and reviews data and presents novel analyses of these from a rat model of contusion injury that demonstrates how a targeted intervention can accelerate recovery, presumably by engaging processes that underlie activity‐dependent plasticity.